From Offline to Online : Transformasi Inovasi Bisnis UMKM Desa Karangasem dengan E-commerce di Era Digital - Rismaya Nikmatul Hida Saskia Putri (Pusat Riset dan Inovasi Nasional, 2025)
This study explores the case of MSMEs (Micro, Small, and Medium Enterprises) in Karangasem Village undergoing a transformation from offline to online business systems through the adoption of e-commerce in the digital era. The main issue examined is the limited market reach and lack of business innovation faced by local MSME actors, with the aim of exploring the digital transformation process and its impact on business development. A qualitative approach was employed, using data collection techniques such as in-depth interviews, observation, and documentation involving several MSME actors in the village. The findings indicate that the implementation of e-commerce has brought significant changes in marketing, distribution, and order management. However, challenges such as limited digital skills and inadequate internet infrastructure still persist. The synthesis of ideas reveals that technological training and collaboration among entrepreneurs are key factors for successful transformation. In conclusion, the business transformation of Karangasem Village MSMEs through e-commerce has great potential to enhance competitiveness, but requires continuous support to effectively adapt within the digital ecosystem.